Pedagogical grammar as the framework of research in teaching foreign languages part 2. native language acquisition: general background - Chernovaty, L. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The paper deals with the problems of the native language acquisition, focusing on the notions of ‘cognitive organizer’, ‘language acquisition device’ and ‘language universals’, as well as their role in language acquisition. The analysis allowed concluding that the ‘cognitive organizer’ concept partially coincides with the notion of ‘language acquisition device’. The author argues in favour of the term ‘cognitive organizer’, as it is not limited to language acquisition only, but embraces the individual’s intellectual development in general. Chomsky’s arguments concerning the language acquisition device operation are reviewed, as well as the problems related to the language acquisition device model interpretation. The article analyses two versions of the Language Universals theory: formal and substantive universals within Chomsky’s model and the three-level system of universals in Greenberg’s approach. The author finds them to be predominantly non-contradictory, but rather complementary. The notion of innate universals is analysed based on the ‘marked vs unmarked rules’ opposition. The two models of the Innate Universal Grammar Theory (maturationism and constructivism) are reviewed. Arguments in favour of each of them are analysed.Basing on the analysis, the author concludes that some data could be interpreted as the ones supporting the maturational model. On the other hand, it is difficult to reject the idea of restructuring, which virtually penetrates the entire native language acquisition process, provided the restructuring is seen as a permanent reorganization of the child’s grammar mechanisms. The author arguesin favour of the further research directed at the establishment of the degree of similarity between the native language acquisition, on the one hand, and the foreign language acquisition – on the other. The data obtained in such research should be taken into account in the process of Pedagogical Grammar development.